CDK2 suppression synergizes with all-trans-retinoic acid to overcome the myeloid differentiation blockade of AML cells. (January 2020) - Shao, Xuejing; Xiang, Senfeng; Fu, Huarui; Chen, Yingqian; Xu, Aixiao; Liu, Yujia; Qi, Xiaotian; Cao, Ji; Zhu, Hong; Yang, Bo; He, Qiaojun; Ying, Meidan
Graphical abstract: Abstract: A characteristic feature of leukemia cells is a blockade of differentiation in cellular maturation. All-trans-retinoic acid (ATRA) has been successfully applied for the treatment of M3-type AML (APL, 10 %), but it fails to demonstrate a significant efficacy on the remaining patients with non-APL AML (90 %). Therefore, the research for strategies to extend the efficacy of ATRA-based therapy to non-APL AML is a key avenue of investigation. Here, we evaluate the synergetic effect of CDK2 inhibition and ATRA in AML both in vitro and in vivo . We have determined that both the CDK2 depletion and pharmacological inhibitor of CDK2 significantly sensitize three subtypes of AML cells (including two non-APL cells) to ATRA-induced cell differentiation. RNA-sequence results indicate that transcription activation of differentiation and maturation pathways plays an important role in this synergetic effect. Furthermore, the down-regulation of CDK2 sensitized AML cells to ATRA-induced engraftment prevention of leukemia cells in NOD-SCID mice and promotes the primary AML blasts differentiation when combined with ATRA. Thus, our work not only provides relevant experimental evidence for further validating CDK2 as a target for differentiation therapy, but also uncovers the future clinical application of CDK2 inhibitors in ATRA-based differentiation therapeutics for AML.